Establishment of a method for supplying low melting point alloys for cutting lead waste generated during the decommissioning of nuclear power plants - GOTO, Tomohisa; SUNAGAWA, Takeyoshi; HARVEL, Glenn (Journal of Nuclear Fuel Cycle and Environment, 2025)
Lead is widely used as a shielding material in nuclear power plants (nuclear and radiation facilities), and lead and lead-containing materials contaminated with radioactive materials are generated as waste during decommissioning. The operator must secure a disposal site for waste generated during decommissioning. Therefore, operators reduce waste by treating low-level radioactive waste below the clearance level through a clearance system. This study aimed to establish a method to precisely cut only the contaminated parts with the aim of minimizing the amount of contaminated lead waste. The method involves reacting lead with Bi and Sn to turn the lead into a low-melting-point alloy and then cutting it. For this low-melting-point alloying of lead, a method was examined in which a Bi-Sn alloy was produced and supplied to the lead. As a result of the study, experiments were conducted to confirm the effectiveness of a method in which the Bi-Sn alloy was dripped in liquid form on the lead cutting part and a method in which it was poured in paste form. As a result of the experiment, the method in which the Bi-Sn alloy was poured in paste form on the lead cutting part was superior in precisely cutting the targeted part.